2013
DOI: 10.1177/0032885513501024
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated Fathers and Their Children

Abstract: High incarceration rates have led to more interest in the effects of incarceration on families, especially children. Most research has focused on the relationship between incarcerated mothers and their children. This study centered on father-child relationships and potential barriers to maintaining and developing them. A sample of 185 incarcerated fathers was interviewed within a maximum security state prison in the southern United States. Multiple regression analyses indicated two family barriers (children's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 28 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…In general, compared with single inmates, inmates who have a healthy and stable marriage during incarceration experience many benefits, including mental and physical health and increased well-being (Einhorn et al, 2008). However, male offenders historically receive less social support from their families than female inmates (Eddy et al, 2008;Hairston, Rollin, & Jo, 2004;Swanson, Lee, Sansone, & Tatum, 2013). Hairston et al (2004) reported that when inmates were asked how many visits they received in the last month, 65% of male inmates reported not having a visit from any family member versus 62% of female inmates.…”
mentioning
confidence: 99%
“…In general, compared with single inmates, inmates who have a healthy and stable marriage during incarceration experience many benefits, including mental and physical health and increased well-being (Einhorn et al, 2008). However, male offenders historically receive less social support from their families than female inmates (Eddy et al, 2008;Hairston, Rollin, & Jo, 2004;Swanson, Lee, Sansone, & Tatum, 2013). Hairston et al (2004) reported that when inmates were asked how many visits they received in the last month, 65% of male inmates reported not having a visit from any family member versus 62% of female inmates.…”
mentioning
confidence: 99%
“…The father-child relationship has important implications for both incarcerated fathers and their children. For incarcerated fathers, a self-perception of poor fathering role and fatherchild relationship is associated with higher risk of depression (Hairston, 1998;Swanson et al, 2013); conversely, a perception of a good father-child relationship is associated with an estimated higher level of social support from all sources including family, friends, and significant others (Swanson et al, 2012). Healthy father-child relationships have positive effects on incarcerated fathers during incarceration and after release (Hairston, 2007;Swanson et al, 2013).…”
Section: Father-child Relationship Among Incarcerated Fathersmentioning
confidence: 99%
“…For incarcerated fathers, a self-perception of poor fathering role and fatherchild relationship is associated with higher risk of depression (Hairston, 1998;Swanson et al, 2013); conversely, a perception of a good father-child relationship is associated with an estimated higher level of social support from all sources including family, friends, and significant others (Swanson et al, 2012). Healthy father-child relationships have positive effects on incarcerated fathers during incarceration and after release (Hairston, 2007;Swanson et al, 2013). Fathers with closer relationships with children before and during incarceration are more likely to have higher levels of father involvement, more weekly work hours, and lower recidivism rate after release (Visher et al, 2013).…”
Section: Father-child Relationship Among Incarcerated Fathersmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, fathers’ previous incarcerations, type of offense, and length of the current stay in prison are detention factors that impact father–child contact (Arditti et al, 2005; Clarke et al, 2005; Swanson et al, 2013). For example, Lee et al (2012) noted that incarcerated fathers with multiple convictions were less likely to spend time with their children while incarcerated.…”
Section: Introductionmentioning
confidence: 99%